Mobitz Type II Atrioventricular Block Followed by Remifentanil in a Patient with Severe Aortic Stenosis - Mehryar Taghavi Gilani; Majid Razavi (Case Reports in Anesthesiology)
Opioids have been considered for their hemodynamic stability. Remifentanil is an opioid analgesic with rapid metabolism and fast primary effect and recovery. In this paper, a very rare effect of using remifentanil along with propofol was presented. An 84-year-old male patient with severe aortic stenosis underwent general anesthesia. In order to induce anesthesia and maintain it, fentanyl, pancuronium, and propofol, along with a combination of propofol and remifentanil, were used, respectively. At beginning of remifentanil infusion, bradycardia and then Mobitz type II conduction block with a hemodynamic disorder occurred for the patient. The decreased blood pressure responded to injection of atropine and ephedrine; however, dysrhythmia only improved after cessation of remifentanil. Therefore remifentanil should be used with caution in aortic stenosis.